Publisher Correction: Network inference from glycoproteomics data reveals new reactions in the IgG glycosylation pathway - Elisa Benedetti (Nature Portfolio, 2018)
Correction to: Nature Communications (2017) 8:1231. doi:10.1038/s41467-017-01525-0